2006
DOI: 10.1021/ol062518z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Turn On of Coumarin Derivatives by Metal Cations:  A New Signaling Mechanism Based on C=N Isomerization

Abstract: [reaction: see text] A new sensing mechanism based on C=N isomerization, which shows a very significant fluorescence enhancement to the metal cations in a simple and efficient way, is demonstrated. A coumarin derivative (L) containing a C=N group was designed as an example for illustration. The free ligand L is almost nonfluorescent due to the isomerization of C=N double bond in the excited state. However, the solution of ligand shows about a 200-fold increase of fluorescence quantum yield (about 30%) upon add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
190
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(196 citation statements)
references
References 38 publications
3
190
2
1
Order By: Relevance
“…Together with the viscoelastic properties and biocompatibility, the Mg 2 + hydrogel may find utility as a novel soft material in biomedical applications. Keywords: coordination polymers · fluorescence · hydrogel · magnesium · viscoelasticity tween the metal cations and fluorophores, [13] main group metals do not quench the fluorescence. It has been reported that the fluorescence properties of coumarin derivatives can be retained in the presence of alkali-earth metals and quenched by transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the viscoelastic properties and biocompatibility, the Mg 2 + hydrogel may find utility as a novel soft material in biomedical applications. Keywords: coordination polymers · fluorescence · hydrogel · magnesium · viscoelasticity tween the metal cations and fluorophores, [13] main group metals do not quench the fluorescence. It has been reported that the fluorescence properties of coumarin derivatives can be retained in the presence of alkali-earth metals and quenched by transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…HCl and glacial acetic acid using the reported procedure [48] Compound 2 was subjected to Vilsmeier-Haack reaction using DMF/POCl 3 to give 7-(diethylamino)-2-oxo-2 H-chromene-3-carbaldehyde (3) according to the procedure has been described by Wu et al [48].…”
Section: Synthesis Of Intermediate 2 Andmentioning
confidence: 99%
“…Thet itle compound was synthesized according to published procedures [1][2][3][4]. All chemicals usedw ere commercially available of AR grade, and were used as received without further purification.…”
Section: Source Of Materialsmentioning
confidence: 99%